1988
DOI: 10.1139/v88-327
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular orbital studies of the potential energy curves for the low lying triplet states of Be2 and Be3

Abstract: Ab initio calculations with uniform quality gaussian basis set were carried out at the RHF-SCF and CI level on the potential energy curves of the low lying triplet states of Be2 and Be3. The lowest excited state, the [Formula: see text] state of Be2 is 26.0 kcal/mol higher in energy than the ground [Formula: see text] state, and 39.4 kcal/mol lower than the separated Be(1S0) + Be(3P) atoms, with the s, p, d basis set. The next higher triplet state, the 3Πg, is only 8.7 kcal/mol above the lowest [Formula: see t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In this case, the difficulty comes from the accurate evaluation of the C 6 coefficient ͑and then of the imaginary frequency-dependent polarizabilities͒. However, it can be noted that the behavior at large distance for the two 2 1 Sϩ2 3 P and 2 1 Sϩ2 1 P interactions seems similar to the ones observed at short distance and given by Bruna et al 15 and Gosavi et al 16 The only apparent discrepancies concern the B 1 ⌺ u ϩ potential but we cannot definitely conclude to the repulsive or attractive behavior at distances shorter than the R LR criteria 16.7 and 18.5 a.u. for the singlet-triplet and the singlet-singlet interactions, respectively, if we do not take into account the totality of the exchange contribution.…”
Section: B the Be 2 Dimermentioning
confidence: 67%
See 3 more Smart Citations
“…In this case, the difficulty comes from the accurate evaluation of the C 6 coefficient ͑and then of the imaginary frequency-dependent polarizabilities͒. However, it can be noted that the behavior at large distance for the two 2 1 Sϩ2 3 P and 2 1 Sϩ2 1 P interactions seems similar to the ones observed at short distance and given by Bruna et al 15 and Gosavi et al 16 The only apparent discrepancies concern the B 1 ⌺ u ϩ potential but we cannot definitely conclude to the repulsive or attractive behavior at distances shorter than the R LR criteria 16.7 and 18.5 a.u. for the singlet-triplet and the singlet-singlet interactions, respectively, if we do not take into account the totality of the exchange contribution.…”
Section: B the Be 2 Dimermentioning
confidence: 67%
“…Concerning this kind of molecule for which several theoretical studies have been reported, with results and predictions often quite contradictory, experimen-talists and theoreticians have recently focused specific attention on the study of their low-lying electronic states. 11,[14][15][16] With regard to the dissociative channels, these studies demonstrate that there is a need for high level ab initio investigations on the asymptotic long-range properties.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations